REPRESENTASI EROTIKA DALAM LIRIK LAGU DANGDUT (Analisis Bahasa Kritis Terhadap Lirik LaguDangdut) - Nawiroh Vera (Fakultas Ilmu Komunikasi - Universitas Budi Luhur, 2017)
ABSTRACTDangdut is one of the Indonesia's music genres, and come give a special color in thedevelopment of Indonesian music. Dangdut should be able to become the nation'sprecious asset, but in their own countr. Dangdut is actually considered “musikkampungan” sometimes some people shame and feel no prestige if they love this music.Negative image of dangdut is because of several factors that is the song tittle and thelyrics are vulgar and represent erotica, such as the song